Lugol’s solution for preoperative management of a TSH/GH-secreting pituitary adenoma with suboptimal response to octreotide: a case report - Peng, Guiliang; Lei, Xiaotian; Leng, Weiling; Wu, Feng; Xie, Laiping; Long, Min; Chen, Liu (Frontiers in Endocrinology, 2026)
BackgroundThyroid-stimulating hormone pituitary adenomas (TSHomas) are a rare cause of central hyperthyroidism, characterized by abnormally high TSH levels, and typically respond to somatostatin analogue (SSA). We report a young patient with SSA-insensitive TSHoma where Lugol’s solution facilitated surgical preparation.Case presentationA 28-year-old male patient presented with a 1.5-year history of headache and visual loss. Thyroid function revealed elevated levels of free triiodothyronine (FT3) 45.87 pmol/L, free thyroxine (FT4) exceeding 100 pmol/L, and non-suppressed TSH 6.66 mIU/L. Magnetic resonance imaging (MRI) suggested a large pituitary adenoma (19 × 25 × 23 mm). Initial long-acting octreotide treatment was ineffective in controlling hyperthyroidism and was discontinued after 5 months. Approximately 1 year after the initial presentation, reassessment showed persistently elevated thyroid hormone levels. A TSH suppression test indicated octreotide sensitivity at 55%. An oral glucose tolerance test (OGTT) suggested concomitant growth hormone (GH) excess. Preoperatively, treatment with short-acting octreotide, methimazole, and Lugol’s solution effectively controlled thyroid hormone levels. The patient subsequently underwent transnasal adenomectomy. Histopathology confirmed a PIT-1-positive pituitary adenoma, with TSH, GH, and prolactin (PRL) positivity. At the 3-month follow-up, thyroid hormone, GH, and insulin-like growth factor-1 (IGF-1) levels had normalized.ConclusionsThis case highlights Lugol’s solution as a rescue therapy for SSA-insensitive TSH/GH co-secreting pituitary adenomas. Despite SSTR2/5 positivity, suboptimal response to octreotide suggests tumor heterogeneity or downstream signaling defects. Preoperative Lugol’s solution should be considered when SSAs and methimazole fail.